On the direction of pitchfork bifurcation - Xiaojie Hou; Philip Korman; Yi Li (Electronic Journal of Differential Equations, 2007)
We present an algorithm for computing the direction of pitchfork bifurcation for two-point boundary value problems. The formula is rather involved, but its computational evaluation is quite feasible. As an application, we obtain a multiplicity result.